Involvement of People in the Planning Process - Planning Commission (Planning Commission, 1987)
This report examines the role of people’s participation in India’s planning process, with a focus on participatory mechanisms in place during the late 1980s. It highlights how involving citizens and local institutions helps identify community needs, mobilize resources, reduce conflicts, and improve the effectiveness of development programs, particularly for marginalized groups. Key participatory structures include Panchayati Raj Institutions, cooperatives, and voluntary organizations, which contribute significantly across sectors such as agriculture, health, education, and social welfare. The document also reviews state, district, and block-level planning and implementation frameworks across Indian states and Union Territories, emphasizing inclusive representation of elected officials, local bodies, and non-governmental organizations. State-specific examples illustrate how decentralized and adaptable planning structures enhance accountability, transparency, and responsiveness to local needs. Overall, the analysis underscores that sustained community involvement and multi-level governance are essential for successful planning, efficient implementation, and sustainable socioeconomic development in India.
Government of India Planning Commission
Government of India Planning Commission
Keywords: People’s Participation; Decentralized Planning; Panchayati Raj Institutions; Community Engagement; Cooperative Movement; Voluntary Organizations; District Planning Committees; Grassroots Governance; Inclusive Development; Participatory Monitoring